2022
DOI: 10.1111/1751-2980.13070
|View full text |Cite
|
Sign up to set email alerts
|

Trends of stomach cancer survival: A systematic review of survival rates from population‐based cancer registration

Abstract: Objectives: We aimed to describe the pattern and time trends of survival from stomach cancer worldwide from population-based cancer registers.Methods: A systematic search of PubMed, Web of Science, EMBASE, SEER and SinoMed for articles published up to 31 December 2020 was conducted. All eligible survival analyses of stomach cancer were collected and evaluated by countries or regions, periods, sex and age groups.Results: Our review included 76 articles on stomach cancer survival rates and found that these rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
6
2
Order By: Relevance
“…In addition, a Cameronian study also reveals a 4.6% five‐year survival rate 16 . A previous systematic review shows a relatively poor five‐year survival rate in Africa compared to Korean and Japanese gastric cancer patients 25 . In contrast, the findings in our study reported a significantly higher five‐year survival rate (32.7%) despite the survival rate being reduced from 1 year to the fifth year after the diagnosis of the disease.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In addition, a Cameronian study also reveals a 4.6% five‐year survival rate 16 . A previous systematic review shows a relatively poor five‐year survival rate in Africa compared to Korean and Japanese gastric cancer patients 25 . In contrast, the findings in our study reported a significantly higher five‐year survival rate (32.7%) despite the survival rate being reduced from 1 year to the fifth year after the diagnosis of the disease.…”
Section: Discussioncontrasting
confidence: 94%
“…16 A previous systematic review shows a relatively poor five-year survival rate in Africa compared to Korean and Japanese gastric cancer patients. 25 In contrast, the findings in our study reported a significantly higher five-year survival rate (32.7%) despite the survival rate being reduced from 1 year to the fifth year after the diagnosis of the disease. However, awareness creation education programs about early signs and symptoms of gastric cancer, optimal management and availability of anticancer drugs in all cancer treatment centers are essential to enhance overall survival in our setting.…”
Section: Discussioncontrasting
confidence: 91%
“…Although survival rates in GC have been improving, the 5‐year relative survival rates have remained between 20 and 30% in developed countries by year 2010–2014 9,10 . Survival has reached over 60% in Japan and South Korea where population screening has been implemented 11 …”
Section: Introductionmentioning
confidence: 99%
“…This study only included patients with resectable GC; however, all-comer outcomes are much worse. A recent review of 5-year all-comer survival rates of GC patients between the 1990s and 2010s showed vast differences between countries, with the highest survival rates of 72.1% in Japan, down to 38.4% in America [ 9 ]. Some of this difference may be accounted for by stage at presentation, with a much lower percentage of patients having early, localized disease in the American and European studies as compared to countries with GC screening programs such as South Korea and Japan [ 9 ].…”
Section: Introductionmentioning
confidence: 99%